(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
The search for plant-derived solutions as an alternative to synthetic aquarium water conditioners has driven interest in aquaculture due to the linkage of poor water management to environmental degradation and ecosystem imbalance. This study assessed the effectiveness of lyophilized Terminalia catappa leaf extract as a natural algicide and water conditioning agent in aquaria containing Poecilia reticulata. Three concentrations (500, 1000, 1500 ppm) were tested, alongside negative and positive controls during the 30-day experiment. Throughout the study, water quality parameters, algal proliferation, and fish survival were monitored. The treatment groups exhibited improved survival, compared to the untreated control. 1000 and 1500 ppm significantly delayed and reduced algal growth. The extract stabilized water conditions and maintained water quality parameters within biologically acceptable ranges. These findings demonstrate the efficacy of lyophilized T. catappa leaf extract as an eco-friendly and sustainable alternative to conventional water conditioners. This study can benefit both environmental health and resource-efficient fish production by promoting plant-based strategies that reduce reliance on synthetic chemicals. Additionally, this study supports the United Nations’ Sustainable Development Goals: SDG 6 (Clean Water and Sanitation) by improving water and quality management, SDG 12 (Responsible Consumption and Production) through the use of natural and biodegradable materials, and SDG 14 (Life Below Water) by minimizing ecological risks associated with chemical pollutants in aquatic systems.